Redefining Language Learning: The Impact of AI Technology on Second Language Acquisition - Ni, Yueheng (Transactions on Social Science, Education and Humanities Research, 2024)
Second language acquisition (SLA) is a complex long-term process which is time-consuming and requires a huge number of resources. However, with the advance of technology, artificial intelligence (AI) has been gradually integrated into the aspect of SLA which provides great convenience for more people to get access to artificial intelligence education (AIED). As both AI technology and the Internet continuously evolved, the AIED in SLA showed great benefits to society and this is the reason for its widespread among students. While AI is bringing great efficiency and accuracy to the SLA, it is important for society to pay attention to the potential disadvantages that using AI might bring to the learners, such as the fear of communicating with real native speakers after the long-term learning accompanied by AI. This paper gives a systematic review of the AI technology that has been used throughout the SLA and presents both its positive and negative feedback to make people aware of the future impact that AI might bring to society. In addition, this paper includes the future directions and suggestions for better development of AI in the field of SLA which enables the AIED to highlight its benefits and eliminate the potential risks.